Rare bird documentation form for Lesser Black-backed Gull at Spring Run Wetland Area - Lair Tract, 1998 - Schoenewe, Lee A.et al (1998)
Rare bird documentation form for a Lesser Black-backed Gull at Spring Run Wetland Area - Lair Tract in Dickinson County, IA on November 8, 1998. Epson - sheet feed